Introducing the Wunderkammer as a tool for emotion research: Unconstrained gaze and movement patterns in three emotionally evocative virtual worlds. (June 2016) - McCall, Cade; Hildebrandt, Lea K.; Hartmann, Ralf; Baczkowski, Blazej M.; Singer, Tania
Abstract: Here we introduce the "Wunderkammer", a suite of immersive virtual worlds with different types of emotionally-charged content. We use these worlds to examine the effects of affective context on unconstrained gaze and movement. In the Affect Gallery, participants freely explored a virtual art museum filled with objects that varied in valence and arousal. Participants approached and gazed more at positively valenced objects. This preference was amplified by more arousing objects and was strongest among individuals with resilient emotion regulation tendencies. This bias of avoiding negative valence did not emerge in The Crowded Room, an environment in which participants encountered virtual humans expressing different emotions. Instead, participants gazed more at negative than neutral emotional displays although they physically avoided angry (but not sad or neutral) agents. When placed inside Room 101, an unpredictable environment filled with a series of disturbing events, frightened participants became relatively immobile in terms of both gaze and movement. This freezing-type response was particularly strong among dispositionally resilient individuals. Together these results demonstrate that distinct affective contexts elicit unique patterns in unconstrained gaze and movement. They further illustrate the benefits of using virtual reality to study affect as it naturally emerges. Highlights: Here we introduce a suite of virtual worlds designed to study affect. We measured unconstrained gaze and movement as participants explored these worlds. Approach and avoidance patterns emerged in response to both agents and objects. Freezing-type fear responses emerged within a pervasively threatening environment. "Virtual ethology" offers a naturalistic means of studying human affect.